THE IMPACT OF TEACHING AND LEARNING ONLINE DURING COVID-19 PANDEMIC ON PRIMARY SCHOOL IN RURAL AREA: A CASE STUDY: Studi kasus tentang pembelajaran online di salah satu SD di area pedesaan kecamatan Widang Kabupaten Tuban, selama Pandemi Covid-19 - Wahyuningsih, Irma (Prosiding SNasPPM, 2021)
During Covid-19 pandemic in Indonesia, teaching and learning should done in online. The purpose of this research to explain the perspectives about benefits and bad impacts of teaching and learning online of primary school teachers and parents in rural area. This study used a qualitative. The respondent of this study were 6 parents and teacher in a village Widang Sub-district of Tuban Recency. The researcher given initials R1, R2, R3, R4, R5, and R6. Using semi- structured interviews were conductedand a list of questions compiled for interviews was developed based on the related literature. The result of the study, there are many bad impact of the students, parents, and teachers. The transformation between face-to-face learning on online learning.